A smart researching and planning tool for the neuralgic urban zone: 3D-ZPA. - Psenner, Angelika (My University, 2014)
Vorgestellt wird ein Aufnahmetool (3D-ZPA = 3-Dimensionale Zusammenhängende Parterre-Aufnahme), mittels dessen Leerstandssituationen im Maßstab von Straßenzügen zusammenhängend dokumentiert und auf ihre lokalen ökonomischen und sozialen Hintergründe befragt werden. Längerfristig soll damit die systematische Bestandsaufnahme der baulichen Struktur und die Inventarisierung der tatsächlichen und der möglichen Nutzungen auf Quartierebene im Sinne eines anwendbaren Planungsinstruments etabliert werden. Konkret wird ein Aufnahmedokument angestrebt, das Grundlage für die Artikulierung von generellen Ansichten über das Wiener Parterre, die Entwicklung praktischer Richtlinien für zukünftige quartiersbezogene Intervention und die (Um)Gestaltung einzelner Straßenzüge sein wird.

A simple cadastral map (Katasterplan) or the multi-purpose map in use in Vienna (Mehrzweckkarte) show only the perimeter of the buildings; they do not provide a sufficiently objective representation and description of the interior structure of the city. A comprehensive plan ZGA (Zusammenhängende Grundrissaufnahme) of the ground floor level yields information about a building s relationship to public space and the topographical environment: it visualizes the interrelation between the interior life of individual buildings and the public street space surrounding them. The comprehensive plan of the ground floor level together with the comprehensive plan of the basement level (very often ZGAs cover different levels, mostly: ground floor, basement and standard upper floor are consequently used to examine the relationship among buildings, streets, and yards. The present study s primary objective is to reproduce and to model the three-dimensional sphere of the urban street-level environment (StadtParterre) in Vienna. To this end, the ZGA, described above, was developed further into the so called: 3D-ZPA (3-Dimensionale Zusammenhängende Parterre-Aufnahme).
Keywords: Stadtplanung; Straßenraum; Raumnutzung; Grundriss; Kartographie; Methode; Planungshilfe; Visualisierung; Stadtgrundriss